Fish oil alleviates diabetes-induced aortic endothelial dysfunction and injuries in mice - Dongyan Song; Huali Meng; Jian Zhou; Xiaoli Huang; Lei Du; Hao Wu (Journal of Agriculture and Food Research, 2024)
Diabetes mellitus (DM)-induced endothelial dysfunction (DED) contributes to macrovascular complications of DM, resulting in high mortality. Fish oil (FO) is a dietary source of omega-3 polyunsaturated fatty acids, with little known for its action on DED. Thus, the objective of the current study was to investigate the effect of FO on aortic DED using a mouse model of DM. To this end, C57BL/6 J male mice (n = 8/each group) were intraperitoneally injected with streptozotocin (50 mg/kg/day, 5 days), following feeding with a high-fat diet containing FO for 24 weeks, with fasting blood glucose levels and glucose tolerance monitored. At the end of the procedure, aortic rings were harvested and evaluated for the contraction and relaxation in response to phenylephrine and acetylcholine respectively. Aortic pathological injuries were assessed by hematoxylin and eosin, and Masson's trichrome staining. Aortic expression of proinflammatory, oxidative stress and profibrotic markers were determined by qRT-PCR and immunohistochemical staining. The diabetic mice developed impaired glucose tolerance, abnormal endothelial dependent aortic contraction and relaxation, thickened tunica media, and increased accumulation of fibrosis in the aortas. These effects were remarkably reversed by FO supplementation. Further investigation revealed that FO inhibited aortic mRNA expression of Tnf-α, Il-6, Il-1β and Vcam-1 as markers for inflammation, Nox1, Nox2, Nox4 and Nos2 as markers for oxidative stress, as well as Acta 2, Col1a1, Col3 and Ccn2 as markers for fibrosis. Moreover, FO decreased the aortic protein expression of TNF-α, 4-HNE and COL1, all of which were increased under the diabetic condition. The present study may provide a molecular basis for the application of FO in prevention of macrovascular complications of DM.